Dense CO2 antisolvent precipitation of levothyroxine sodium: A comparative study of GAS and ARISE techniques based on morphology and particle size distributions - De Melo, S.; Danh, L.; Mammucari, R.; Foster, Neil (Elsevier BV, 2014)
© 2014 Elsevier Ltd. All rights reserved. Morphology and particle size distribution of levothyroxine sodium are experimentally investigated by comparing gas antisolvent (GAS) and atomized rapid injection for solvent extraction (ARISE) techniques using dense CO 2 . Precipitation of levothyroxine sodium from ethanol was carried out at 25, 40 and 50 °C, with pressure in the 90-120 bar range and different concentrations of the organic solution. Particles produced by the GAS process are nanospheres whereas ARISE processed particles are either spherical or rod-like micro and nanoparticles. Particle size and size distributions of GAS processed levothyroxine sodium are in the 370-500 nm range, while the ARISE process produced particles in the 360-1200 nm range. In most cases, both techniques produced bimodal size distributions, due to particle agglomeration. The different morphological characteristics and particle size distributions of levothyroxine sodium obtained using GAS and ARISE at different operating conditions can be useful depending on the type of drug formulation chosen, as well as the route of drug administration and delivery system.